2019
DOI: 10.1038/s41598-019-54840-5
|View full text |Cite
|
Sign up to set email alerts
|

MSC Transplantation Improves Lacrimal Gland Regeneration after Surgically Induced Dry Eye Disease in Mice

Abstract: Dry eye disease (DED) is a multifactorial disease characterized by a disrupted tear film homeostasis and inflammation leading to visual impairments and pain in patients. Aqueous-deficient dry eye (ADDE) causes the most severe progressions and depends mainly on the loss of functional lacrimal gland (LG) tissue. Despite a high prevalence, therapies remain palliative. Therefore, it is of great interest to develop new approaches to curatively treat ADDE. Mesenchymal stem/stromal cells (MSC) have been shown to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 58 publications
2
36
0
Order By: Relevance
“… 16 It has been found that injection of mesenchymal stem cells or mesenchymal stem cell secretomes can help lacrimal gland regeneration. 41 , 42 In the current study, the number of mesenchymal cells increased in response to two weeks of stimulation with lacrimal duct obstruction. However, longer-term duct obstruction will lead to a decrease in the number of vimentin-positive cells, and it is speculated that the imbalance of lacrimal gland homeostasis at this time leads to cell differentiation or death.…”
Section: Discussionsupporting
confidence: 49%
“… 16 It has been found that injection of mesenchymal stem cells or mesenchymal stem cell secretomes can help lacrimal gland regeneration. 41 , 42 In the current study, the number of mesenchymal cells increased in response to two weeks of stimulation with lacrimal duct obstruction. However, longer-term duct obstruction will lead to a decrease in the number of vimentin-positive cells, and it is speculated that the imbalance of lacrimal gland homeostasis at this time leads to cell differentiation or death.…”
Section: Discussionsupporting
confidence: 49%
“…The injections of DFMSCs were done with three injection ways as described before [ 10 12 ] with some modifications as follows; I) İntraperitoneal injection: 1x10 6 cells suspended in 0.5 mL of PBS was injected intraperitoneally with a 28-gauge needle [ 10 ]. II) Submandibular gland injection: 1x10 6 cells suspended in 0.1 mL PBS, and injected in the submandibular gland below the throat line of the mouse with a 29-gauge needle [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…II) Submandibular gland injection: 1x10 6 cells suspended in 0.1 mL PBS, and injected in the submandibular gland below the throat line of the mouse with a 29-gauge needle [ 11 ]. III) Lacrimal gland injection: 1x10 6 cells suspended in 20 μL PBS was injected in the extra orbital lacrimal gland through the front of the ear line with a 27-gauge needle [ 12 ]. All injections were done on day 126.…”
Section: Methodsmentioning
confidence: 99%
“…injection, showed that, despite a positive temporary effect of this treatment on the lacrimal gland function, BMSC did not engraft into the epithelial component of the gland [264]. Several other studies also reported the therapeutic benefits of MSCs, even though engraftment of these cells into the epithelial compartment of the lacrimal gland was not detected [265,266].…”
Section: Mesenchyme Stem Cells Transplantationmentioning
confidence: 96%